Het laatste Joegoslavische elftal . The Last Yugoslavian Football Team - Janic, Vuk (Pieter van Huystee Film, 2000)
Born in the same country, they became world youth champions in Chile in 1989; the 'Chileans' played together until 1990. Then war broke out and Yugoslavia started to fall apart. First the Croatian players left, then the trainer Ivica Osim resigned because the Serbians bombed his home town of Sarajevo. Under pressure of the international community, the team was banned from the European championships in Sweden. In March 1999 they were to share the same soccer pitch for the first time in a direct clash during the preliminary rounds of the Euro 2000 Championship. But this very tense qualification match between Yugoslavia and Croatia was again postponed because of war, this time in Kosovo. In August 1999 the game was played in Belgrade. Two months later the return game was played in Zagreb (Croatia). Players who knew each other intimately, grew up together and were world champions together, were now divided by contradictory interests as a result of the war. The war forced each of them to choose a new fatherland, a new nationality, a new national anthem and a new national football team. This film is his story about a country falling apart, told by its former heroes - the 'Chileans'.